Paraneoplastic glomerular disease: The struggle is real. Issue 1 (February 2019) - Amarapurkar, Pooja; Bou-Slaiman, Salim; Madrid, Bianca; Ladino, Marco
Over the past decade, the relationships between various kidney disease and cancer have been established, but not fully elucidated. Development of acute kidney injury or chronic kidney disease as a side effect of cancer treatment is not uncommon. However, renal paraneoplastic diseases are rather unique and less known examples of the association between kidney disease and cancer. These conditions are of importance to the nephrologist as they may be the initial presentation of an underlying malignancy and may not respond to the usual therapies used for their non-paraneoplastic variants. This article will discuss the pathogenesis and challenges in management of paraneoplastic glomerular diseases.